Design of a technopedagogical experience as a tool for the critical management of information: intervention with higher education students in Peru - Rojas-Estrada, Elizabeth-Guadalupe (2025)
By fostering critical thinking and reflection regarding the media, educommunication empowers citizens to question media content, make informed decisions, engage in public debates and contribute to the strengthening of democracy. This article aims to present the design of a technopedagogical experience developed to promote critical information management among higher education students in Peru, contextualized within the sociopolitical crisis of 2022-2023. To implement this initiative, a website has been created that hosts four modules, which have been designed following the ADDIE protocol (Analysis, Design, Development, Implementation and Evaluation), an iterative framework of instructional design that allows the structured development of educational content. This experience involved the participation of 52 students from five higher education institutions. The results of the analysis indicate that, following the intervention, participants identified new strategies for analyzing and producing information, as well as for acting in digital spaces, which underlines the relevance of this type of training proposals. Additionally, the use of technopedagogical experiences is highlighted as an effective methodological tool for data collection.